Becoming past : history in contemporary art - Blocker, Jane (University of Minnesota Press, 2016)
History as prosthesis -- Wooden legs: Goat Island's acts of repair -- Houses falling down: archival violence in Steve McQueen's Deadpan -- Incorrect and incomplete: Ross McElwee's fictions and Samuel Delany's lies -- The empty stage: a story about the past by Matthew Buckingham -- Stupid birds: temporal dissidence in The Lastmaker -- Transitional objects: Dario Robleto's spools -- Wooden feet: Francis Alÿs and syncopated time.